Correlation between malondialdehyde (MDA) and uric acid levels in preeclampsia - Krishna, T. Sharmila; Rao, E. Venkata; Sowjanya, B.; Saseekala, A.; Naidu, J. N. (International Journal of Research in Medical Sciences, 2017)
Background: Hypertensive disorders of human pregnancy, such as preeclampsia, complicates a sizeable percentage of all pregnancies, need its early indication and warning. The aim of present study was to determine the association between lipid peroxidation product, serum malondialdehyde (MDA) and serum uric acid levels in preeclampsia and find out any association between these two parameters in preeclampsia. Methods: Thirty preeclampsia and thirty gestational age matched normotensive pregnant women attending Narayana General Hospital, Nellore were included in the study. Serum MDA levels were measured by Thiobarbituric acid reactive substances(TBARS) method and serum uric acid levels were estimated by automated chemistry analyser using commercial kits. Results: Serum MDA (Mean±SEM 24.4±2.38 vs 7.9± 0.28 nmol/ml, p value < 0.000) and serum uric acid levels (7.2 ± 0.25 vs 3.9 ± 0.14 mg/dl, p value <0.000) were significantly elevated in preeclampsia cases when compared with that of normotensive pregnant women. A weak positive correlation between serum uric acid and serum MDA (r value 0.065, p value 0.734) was noticed in preeclampsia. Conclusion: Serum MDA and uric acid may be included as additional markers for screening and progression of preeclampsia, thereby helpful in effectively treating the condition at an early stage.